Distribution characteristics of some zoobenthos species at the De Gi lagoon, Binh Dinh province - Ngai, Phan Duc; Tuan, Vo Si; Hai, Doan Nhu (Academia Journal of Biology, 2015)
Distribution characteristics of some zoobenthos species at the De Gi lagoon was reported as results of two surveys carried out during 2009-2010. The results have pointed out bivalve groups are distributed mainly on tidal sandy flats, near estuary and mangroves, where were small density of phytoplankton and organic carbon content in the sediments. Scylla serrata is distributed mainly on tidal sandy flats, where big density of micro-zooplankton was observed in mangroves. Crassostrea cf. lugubris, Scylla serrata and Penaeus monodon are distributed in De Gi lagoon in seed stage. The results of this study can be considered as an important scientific basis for futrher studies on the relating benthic resources focusing on ecological factors and data for planning, zoning and exploitation of appropriately fisheries resources.